2019
DOI: 10.1002/brb3.1512
|View full text |Cite
|
Sign up to set email alerts
|

Nontraumatic spontaneous intracerebral hemorrhage: Baseline characteristics and early outcomes

Abstract: Background and PurposeHemorrhagic stroke, particularly nontraumatic spontaneous intracerebral hemorrhage (SICH), is a cerebrovascular condition with unfavorable outcomes. The aims of the present study were to evaluate patients who suffered from SICH and investigate the early outcomes in a single‐center study.MethodsDuring a study ‐period of 6 years (2008–2014), 613 consecutive patients (mean age, 72 ± 12.7 years; 51.1% female), who suffered from nontraumatic SICH and were treated at the Department of Neurology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 25 publications
2
10
1
Order By: Relevance
“…These outcomes were similar to another study, which indicated large hematoma volume, male gender, deep bleeding site, and age between 51 and 60 years were the related factors of poor short-term prognosis in ICH [ 38 ]. A recent study reported by Al-Khaled et al indicated that the elderly and the patients with severe neurological injury showed lower survival rate, and the gender, history of hypertension, and bleeding site were relevant to prognosis of ICH [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…These outcomes were similar to another study, which indicated large hematoma volume, male gender, deep bleeding site, and age between 51 and 60 years were the related factors of poor short-term prognosis in ICH [ 38 ]. A recent study reported by Al-Khaled et al indicated that the elderly and the patients with severe neurological injury showed lower survival rate, and the gender, history of hypertension, and bleeding site were relevant to prognosis of ICH [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among etiologies, hemorrhagic stroke accounts for approximately 15% of patients [2,3]. Spontaneous intracerebral hemorrhage (sICH) is associated with a high risk of short-term mortality and long-term functional dependence [3,4]. The most frequent pathophysiological mechanism causing sICH is chronic arterial hypertension with development and eventual rupture of microscopic pseudoaneurysms of penetrating arteries typically localized in the basal ganglia, thalami, pons, midbrain and cerebellum [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…50,51 Infection complications were reported to occur in 20-31% of patients with ICH as a risk factor for a poor prognosis. [52][53][54][55] In fact, acute brain injury could lead to immunosuppression due to the dysregulation of brain-immune interactions, which accounts for the high incidence and poor prognosis of coinfection in ICH. Meanwhile, it has been noted that the use of glucocorticoids and rituximab in ITP patients exposes them to a higher risk of infection.…”
Section: Discussionmentioning
confidence: 99%